International Enterprises In WTO Rules -- A Study Of Research And Development Innovation - Xiang, Ran Meng (2008)
International companies in the implementation of global strategy, speed up the development of enterprises, research and development (R&D, the same below) activities of the creation of a new operasition mechanism and vitality, from the traditional mode of research and development to the WTO under the new R&D strategy change in order to rapidly improve their ability in innovation , adaptability and efficiency.